Active Heterogeneous CaO Catalyst Synthesis from Anadara granosa (Kerang) Seashells for Jatropha Biodiesel Production - Reddy, Anr; Aa, A. Saleh; Md Saiful, Islam; Sinin, Hamdan (EDP Sciences, 2016)
Heterogeneous catalysts are often used at large to produce biodiesel from non-edible vegetable crude oils such as Jatropha curcas oil (JCO). In this study, an active heterogeneous CaO catalyst was synthesized from a tropical biodiversity seashells Anadara granosa (A.granosa). The catalytic efficiency of A.granosa CaO was investigated in transesterification of JCO as biodiesel. The A.granosa CaO catalyst was synthesized using 'Calcination - hydration - dehydration' protocol. The spectral characterization of the catalyst were investigated by employing FT-IR, SEM, BET and BJH spectrographic techniques. The experimental design was executed with four reaction parameters that include catalyst concentration (CC), methanol ratio (MR), transesterification time (TT) and reaction temperature (RT). The JCO transesterification reactions as well as impact of reaction parameters on the Jatropha biodiesel yield (JBY) were analyzed. The sufficiency of the experimental results conformed through sequential validation tests, as a result, an average of 96.2% JMY was noted at optimal parametric conditions, CC of 3wt. %, TT of 120 min, MR of 5 mol. and RT of 60C at a constant agitation speed of 300rpm. An average JMY of 87.6% was resulted from the A.granosa CaO catalyst during their recycling and reuse studies up to third reuse cycle